Analysis of regulating activities of 5′-epiequisetin on proliferation, apoptosis, and migration of prostate cancer cells in vitro and in vivo - Wang, Xueni; Luo, Xiaowei; Gan, Xia; Chen, Chunmei; Yang, Zaizhun; Wen, Jing; Fang, Wenxuan; Huang, Hailing; Gao, Chenghai; Zhou, Xuefeng; Feng, Xiaotao; Liu, Yonghong (Frontiers in Pharmacology, 2022)
Advanced prostate cancer has a poor prognosis, and it is urgent to develop new effective drugs. 5'-Epiequisetin is a tetramic acid derivative which was isolated from a marine sponge-derived fungus Fusarium equiseti in our previous study. In this study, 5'-epiequisetin showed cytotoxicity against four prostate cancer cell lines, including LNCaP, 22Rv1, DU145, and PC-3 cells, with the lowest IC50 value of 4.43±0.24 μM in PC-3 cells. Further studies showed that it could dramatically regulate the clonal colonies formation, apoptosis, and migration of PC3 cells. Besides, flow cytometry data showed that 5'-epiequisetin could block cell cycle at G1 phase. Proteome profiler array and western blot revealed that 5'-epiequisetin could regulate the expression of proteins responsible to cell proliferation, apoptosis, and migration. 5'-Epiequisetin regulated the expression of PI3K, AKT, phosphorylated Akt and proteins which control the cell cycle. Meanwhile, 5'-epiequisetin up-regulated expression of DR5 and cleave-caspase 3 which play important roles in the process of apoptosis. Moreover, when DR5 was silenced by small interfering RNA, the proportion of apoptotic cells induced by 5'-epiequisetin was remarkably declined. While 5'-epiequisetin down-regulated expression of survivin which plays key roles in the process of survival and apoptosis. 5'-Epiequisetin also showed impact on beta-catenin and cadherins which were associated with cell migration. In addition, 5'-Epiequisetin significantly inhibited the progression of prostate cancer in mice accompanied with regulating the protein expression of DR5, caspase 8, survivin, and cadherins in vivo. Taken together, these findings indicated 5'-epiequisetin showed anti-prostate cancer effect by inducing apoptosis and inhibiting cell proliferation and migration both in vitro and in vivo, suggesting a promising lead compound for pharmacotherapy of prostate cancer.